2008
DOI: 10.1002/app.27296
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different compatibilisers on nanoclay dispersion, thermal stability, and burning behavior of polypropylene–nanoclay blends

Abstract: ABSTRACT:The dispersion of nanoclays in nonpolar polypropylene (PP) is difficult without the use of a small fraction (1-3%) of modified grafted PP as a compatibiliser. This work reports the effect of different graft-modified polypropylenes on the dispersion of nanoclays in PP, and thermal stability and flammability of the blends. PP has been compounded in a Brabender compounder with a selection of modified PP polymers as compatibilisers. The grafts include maleic anhydride, N-ethylmaleimide, diethylmaleate, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 14 publications
(26 reference statements)
0
15
0
Order By: Relevance
“…Hence, the dispersion of SBA‐15 within the PE matrix may be further decreased when IFR are present. A decreased dispersion should adversely affect the burning behavior . In that respect, it is also worth recalling that the formation of a physical barrier has a limited effect on the results obtained by UL‐94 V and LOI tests.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the dispersion of SBA‐15 within the PE matrix may be further decreased when IFR are present. A decreased dispersion should adversely affect the burning behavior . In that respect, it is also worth recalling that the formation of a physical barrier has a limited effect on the results obtained by UL‐94 V and LOI tests.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the importance of melt intercalation, the effects of processing conditions on the material's properties are not studied very extensively [5]. Most studies deal with the MMT modification and the better dispersion of organoclay in the polymer matrix and also different compatibilizers besides PP‐ g ‐Ma were investigated [6–12]. A novel approach to prepare PP nanocomposites with OH groups as compatibilizer was first reported in 1997 [13].…”
Section: Introductionmentioning
confidence: 99%
“…Polypropylene grafted with diethyl-p-vinylbenzyl phosphonate (DEP) with synthetic procedure described elsewhere [15].…”
Section: Depmentioning
confidence: 99%
“…Levels between 1-3% w/w of grafted PP along with sufficient compounding have been shown to improve the dispersion of the clay platelets in the PP matrix. In a parallel study we have studied the optimisation of nanoclay dispersion in polypropylene by observing the effect of different graft copolymeric modifications of PP [15]. It was found that diethyl-p-vinylbenzyl phosphonate (DEP) and maleic anhydride (commercially available as Polybond 3200) -grafted PP gave the best results for improving the dispersion of the functionalised clays (Cloisite 20A, Southern Clay Products, USA and Elementis Bentone 107 (E107), Elementis Specialities Inc).…”
Section: Introductionmentioning
confidence: 99%